Evaluasi Implementasi Sistem Keselamatan dan Perlindungan Sosial pada Proyek Gedung Bertingkat InaTEWS BMKG - Nurokhman; Hery Kristiyanto; Mochmad Arif Budiyanto (Institut Teknologi Garut, 2026)
The construction of the InaTEWS Operational System Development Buildings in Jakarta and Bali, funded by the International Bank for Reconstruction and Development (IBRD), has a high level of occupational safety risk due to the complexity of the work and the characteristics of multi-storey buildings. Therefore, the implementation of Occupational Health and Safety (OHS), grievance mechanisms, and the prevention of Gender-Based Violence (GBV), child exploitation, and Sexual Exploitation and Abuse (SEA) are important aspects in ensuring the smoothness and sustainability of the project. This study aims to analyze the implementation of OHS, grievance mechanisms, and the prevention of GBV and SEA in the InaTEWS Building construction project. The research method uses a descriptive qualitative approach with a case study through field observations, interviews, questionnaires, and documentation studies. The analysis was carried out by comparing the research findings with the Construction Safety Management System (SMKK) standards based on Government Regulation Number 50 of 2012 and the World Bank’s social protection framework. The results show that the allocation of construction safety costs amounting to 3.60 percent of the project value supports the optimal implementation of OHS. Evaluation of five main elements comprising 82 assessment parameters showed a compliance level of 100 percent, placing it in the satisfactory category. In addition, the grievance mechanism and the prevention of GBV and SEA have been implemented effectively, with no violations found during the research period, and have contributed significantly to achieving the zero-accident commitment, reflecting the effectiveness of the project management system in multi-storey building construction.